The effect of being informed on receiving immediate breast reconstruction in breast cancer patients. Issue 5 (May 2018) - de Ligt, K.M.; van Bommel, A.C.M.; Schreuder, K.; Maduro, J.H.; Vrancken Peeters, M.T.F.D.; Mureau, M.A.M.; Siesling, S.; ,
Abstract: Introduction: In previous research from the NABON breast cancer audit, observed hospital variation in immediate breast reconstruction (IBR) rates in the Netherlands could not be fully explained by tumour, patient, and hospital factors. The process of information provision and decision-making may also contribute to the observed variation; the objective of the current study was to give insight in the underlying decision-making process for IBR and to determine the effect of being informed about IBR on receiving IBR. Methods: A total of 502 patients with IBR and 716 without IBR treated at twenty-nine hospitals were invited to complete an online questionnaire on obtained information and decision-making regarding IBR. The effect of being informed about IBR on receiving IBR was determined by logistic regression analysis. Results: Responses from five hundred and ten patients (n = 229 IBR, n = 281 without IBR) were analysed. Patients with IBR compared to patients without reconstruction showed a difference in patient, tumour, treatment (including radiotherapy), and hospital characteristics. Patients with IBR were more often informed about IBR as a treatment option (99% vs 73%), they discussed (dis)advantages more often with their physician (86% vs 68%), and they were more often involved in shared decision-making (91% vs 67%) compared to patients without IBR. Multivariate logistic regression analysis, corrected for confounders, showed that being informed about IBR increased the odds for receiving IBR fourteen times (p < 0.001). Conclusions: The positive effect of being informed about IBR on receiving IBR stresses the importance of treatment information in the decision-making process for IBR.